Experimental study on influence of Na-bentonite on viscosity of cement-bentonite slurry - Zheng Wei; Wei Cui; Ri-cheng Miao (Case Studies in Construction Materials)
The viscosity of cement-bentonite (CB) slurry has an important impact on its construction quality and engineering utility. This study focuses on the mechanism of how Na-bentonite (Na-B) influences the viscosity of CB slurry. Four types of Na-B were selected to prepare bentonite slurry and CB slurry, followed by the design of tests to analyze the viscosity differences. Based on these results, microscopic tests, including X-ray diffraction (XRD), nuclear magnetic resonance (NMR), and field emission scanning electron microscopy (FESEM), were conducted to explain the reasons for the different properties of different bentonite slurries and their CB slurries. The analysis demonstrates that the variation in viscosity of bentonite slurry can be elucidated by the principles of viscosity recovery, low shear viscosity failure, and differences in bentonite composition. Meanwhile, the viscosity of CB slurry is influenced by charge adsorption, hydration products, and the interaction between bentonite and cement.